Ocean's eleven (2001) [videorecording (DVD)] - Soderbergh, Steven, 1963-; Clooney, George; Mac, Bernie; Pitt, Brad, 1963-; Gould, Elliott; Jemison, Eddie; Affleck, Casey, 1975-; Reiner, Carl, 1922-2020-; Damon, Matt; Garcia, Andy; Roberts, Julia, 1967-; Johnson, George Clayton; et al. (Warner Home Video, 2007)
Danny Ocean like his chances. All he asks is that his handpicked squad of 10 grifters and cons play the game like they have nothing to lose. If all goes right, the payoff will be a fat $150 million. All the gang of associates needs to do is stage heists at three major Las Vegas casinos - Bellagio, The Mirage, and the MGM Grand - simultaneously during a popular boxing event. The payoff, divided by 11, you do the math.